2016
DOI: 10.1136/bcr-2015-214255
|View full text |Cite
|
Sign up to set email alerts
|

Solitary plasmacytoma of the mandible: report of two cases

Abstract: Plasma cell neoplasms (plasmacytoma) are discrete, solitary masses of lymphoid neoplastic proliferations of B cells. Plasmacytomas comprise three groups: multiple myeloma, solitary plasmacytoma (SP) and extramedullary plasmacytoma. SP originates as a clone of transformed malignant plasma cells in the bone marrow. SP of the jaw is a rare condition; therefore diagnosis is quite difficult and often results in misdiagnosis. MM is a lymphoproliferative disease the prognosis of which is worse than SP. SP can progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…SP in maxillofacial bones needs to be differentiated from a variety of single destructive osteolytic tumors, such as ameloblastoma, odontogenic keratocyst, primary intraosseous squamous cell carcinoma of the jaw and osteosarcoma. 3 Ameloblastoma occurs mostly in young adults aged 20-40 years, with no gender difference. Ameloblastoma usually occurs in the mandibular molar region and the ramus of the mandible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP in maxillofacial bones needs to be differentiated from a variety of single destructive osteolytic tumors, such as ameloblastoma, odontogenic keratocyst, primary intraosseous squamous cell carcinoma of the jaw and osteosarcoma. 3 Ameloblastoma occurs mostly in young adults aged 20-40 years, with no gender difference. Ameloblastoma usually occurs in the mandibular molar region and the ramus of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the incidence of SP in mandible is 4.4% within the maxillofacial regions. 3 The incidence of SP in maxillofacial bone is low and its clinical symptoms are not specific. So the clinical diagnosis of SP in maxillofacial bones is quite difficult and often leads to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies have reported that in most cases, lesions were observed in the maxilla rather than the mandible. 10 However, there are also reports of anterior mandibular lesions. In this particular case, the lesion was observed in a woman and located in the anterior region of the mandible.…”
Section: Fig 7: Imwg Criteria For Diagnosis Of Myelomamentioning
confidence: 99%
“…SOPs are a rare subset of plasmacytic tumours found in the vertebrae, long bones, zygomatic arch or ribs of dogs (MacEwen et al 1984, Matus et al 1986, Rusbridge et al 1999, Vail et al 2020. In humans, these plasma cell tumours of bone are more commonly referred to as solitary bone plasmacytomas (SBPs) and occur most commonly in the vertebrae, femur and pelvis, though mandibular and maxillary forms have been described (Anil 2007, Kucukkurt et al 2016. It is a rare disease in humans, and men are diagnosed twice as frequently as women (Pham & Mahindra 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, these plasma cell tumours of bone are more commonly referred to as solitary bone plasmacytomas (SBPs) and occur most commonly in the vertebrae, femur and pelvis, though mandibular and maxillary forms have been described (Anil 2007 , Kucukkurt et al . 2016 ). It is a rare disease in humans, and men are diagnosed twice as frequently as women (Pham & Mahindra 2019 ).…”
Section: Introductionmentioning
confidence: 99%